Positive Psychological Capital as a Predictor of Satisfaction With the Fly-In Fly-Out Model - Soares Marques, Nazaré; Lopes, Miguel Pereira; Gonçalves, Sónia P. (Frontiers in Psychology, 2021)
The flexibility of markets and international agreements have lured a growing number of companies to expand their business beyond frontiers in search for new markets and a bigger business network. Specifically, expatriates became keystones to implant and promote the so desired expansion into international markets, Particularly, Fly-in fly-out (FIFO) flexpatriates. Although FIFO work practices are widely used, little is known about how to promote these professionals’ perceived job satisfaction (JS) across the course of their work cycles. That is why the goal of our research is to test the positive psychological capital (PsyCap) applicability to Portuguese FIFO flexpatriates. In the midst of the positive psychology theories, Luthans et al. (2007b) underline that workers are the psychological capital of any organization. Therefore, the development of the PsyCap becomes crucial and also contributes to the promotion of JS, nowadays a construct intertwined with well-being. As such, we developed and applied a HERO–(hope, self-efficacy, resilience, and optimism)–micro-intervention in order to assess whether it moderated the relationship between a FIFO flexpatriates PsyCap and their JS. The research took place over three distinct moments, both PsyCap and JS were measured before and after the HERO micro-intervention, and again 3 months later. The data collected shows that a positive correlation exists between FIFO flexpatriates PsyCap and JS. Moreover, our results pointed out that the micro-intervention enhanced FIFO flexpatriates PsyCap, and also showed that this increase lasted over (at least) 3 months.